IMPACT OF CARE AND FEEDING OF IMPORTED COWS ON REDUCING MILK PRODUCTIVITY AND IMPROVING FERTILITY (Academicia Globe: Inderscience Research, 2021)
The article is based on modern biotechnological methods to increase the milk yield and fertility of cows, the impact of the use of zootechnical and veterinary measures in their feeding and care.